Growth Hormone Deficiency and Treatment in Childhood Cancer Survivors - Pollock, Netanya I.; Cohen, Laurie E. (Frontiers in Endocrinology, 2021)
Growth hormone (GH) deficiency is a common pituitary hormone deficiency in childhood cancer survivors (CCS). Recombinant human GH therapy is available for this population. However, GH and insulin-like growth factor-I have been implicated in tumorigenesis, and so there has been concern over the use of GH therapy in patients with a history of malignancy. Reassuringly, GH therapy has not been shown to increase risk of tumor recurrence. These patients have an increased risk for development of meningiomas, but this may be related to their history of cranial irradiation rather than to GH therapy. In this review, we detail the CCS who are at risk of GH deficiency and the existing evidence on the safety profile of GH therapy in this patient population.